Genetic Variability Related Behavioral Plasticity in Pikeperch (Sander lucioperca L.) Fingerlings - Ildikó Benedek; Béla Urbányi; Balázs Kovács; István Lehoczky; Attila Zsolnai; Tamás Molnár (Animals)
Background: The relationship between genetic diversity and fitness is well understood, but few studies have investigated how behavior influences genetic diversity, or vice versa. We investigated the relationship between feeding behavior (on a pelleted diet) and genetic diversity in pikeperch, a piscivorous species. Methods: A total of 135 juvenile pikeperch from the same stock were grouped into three behavioral groups: pellet consuming, pellet refusing, and cannibalistic. Eighteen microsatellite markers were used to characterize the genetic diversity and structure of individuals. Results: The juveniles were classified into two genetic clusters: one dominated by pellet-consuming individuals and the other by pellet-refusing individuals containing equal proportions of cannibal individuals. Three of the microsatellite markers were under selection, but only one showed significant genetic segregation between the groups. For this marker, the pellet consumption was associated with low fragment length. Individual multilocus heterozygosity was significantly higher in the pellet-refusing group. Conclusions: These results suggest that pellet consumption acts as an uncontrolled selective force during domestication, influencing the genetic variability of domesticated populations. The ability to habituate to pellets has a significant genetic basis. Cannibalism does not affect genetic variability, and the emergence of the trait is independent of the propensity to consume pellets.